PENGARUH KARTU BERGAMBAR MELALUI MODEL PEMBELAJARAN STAD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Kurnia Mayang Sari; Pramudiyanti Pramudiyanti; Rini Rita Marpaung (Universitas Lampung, 2013)
Based on observationin SMAN 3 Kotabumi, student’s critical thinking skill were not optimally developed. Alternative that can be used is picture card media through STAD learning model. This experiment aims to know the improvement of student’s critical thinking skill. This is quasi experiment using pretest posttest group non equivalent design. Sample are students from X3 and X4which selected from population by cluster random sampling method. Quantitative data from the average of pretest, posttest and N-gain which statistically analyzed with t-test using SPSS 17. Qualitative data are student’s critical thinking skill description, learning activities and student’s response about using picture card through STAD model which descriptively analyzed. Result of this experiment showed that student’s critical thinking skill improved significantly in giving reason (48,07%), reconstructing argument (54,28%) and looking for similarity and difference (42,73%). The student’s learning activities in all observed aspects is improved. Student’s activities in teamwork (89,22%), doing discussion (86,27%) and presenting group discussion result (84,31%). The students also give positive response about usingpicture card through STAD model. So, student’s critical thinking skill improved significantly by using picture card through STAD learning model. Keywords: picture card media, STAD learning model, critical thinking skill, Protista